Controlling Supramolecular Assembly through Peptide Chirality - Manosree Chatterjee (5641505) (2025)
Peptide-based self-assembled hydrogels are promising materials for diverse applications due to their biocompatibility, tunable mechanical properties, and ability to form nanostructured networks via noncovalent interactions. One of the most extensively studied hydrogelators, fluorenylmethyloxycarbonyl-diphenylalanine (Fmoc-FF), rapidly self-assembles into a 3D hydrogel capable of encapsulating enzymes and proteins, making it an attractive candidate for drug delivery applications and the protection of oxygen-sensitive biomolecules. However, its fast gelation results in heterogeneous structures and low-density cavities, limiting its uniformity and complicating the handling. Chirality plays a critical role in peptide self-assembly, yet its impact on hydrogel functionality remains underexplored. Here, we investigate how chirality influences the self-assembly kinetics, morphology, and structural properties of all four enantiomeric forms of Fmoc-FF. Using a range of analytical techniques, we tracked the morphological transitions from monomers to supramolecular nanostructures. Hydrogels formed from homoenantiomers displayed greater rigidity and faster gelation, while heteroenantiomeric systems exhibited a slower, three-phase transition from turbid nanospheres to transparent fibrillary gels. This slower gelation may be advantageous for controlled encapsulation, allowing for homogeneous distribution of the cargo. Finally, all enantiomeric hydrogels effectively prevented oxygen diffusion through their nanofiber networks, allowing H2 production by the oxygen-sensitive enzyme hydrogenase, which was encapsulated within the hydrogels. These findings highlight the potential of enantiomeric design in developing peptide hydrogels for various applications, particularly the encapsulation of small molecules and large proteins as well as oxygen-sensitive processes.